Reduction of Salmonella spp. populations in Italian salami during production process and high pressure processing treatment: Validation of processes to export to the U.S. (November 2019) - Bonilauri, Paolo; Grisenti, Maria Silvia; Daminelli, Paolo; Merialdi, Giuseppe; Ramini, Mattia; Bardasi, Lia; Taddei, Roberta; Cosciani-Cunico, Elena; Dalzini, Elena; Frustoli, Maria Angela; Giacometti, Federica; Piva, Silvia; et al.
Abstract: This study involved ten enterprises producing Italian salami, 20 different samples of fermented sausages underwent challenge tests to assess and record the following parameters: time, temperature, pH, a w, and Salmonella counts. A linear regression model was used to describe the Salmonella spp. decay: at the end of the process the result of total Salmonella reduction was 0.97–5.84 Log10 CFU/g and it was significantly associated with pH at the end of acidification/drying process, a w at the end of seasoning period, the duration of seasoning, and the caliber of salami respectively. High Pressure Processing (HPP) further reduced the Salmonella level by 2.41–5.84 Log10 CFU/g with an efficacy that resulted inversely associated with a w of salami at the end of seasoning; the objective of 5-Log reduction was always reached in all the cases tested by the production process plus HPP. This model could be a useful tool for enterprises and Authorities to evaluate the efficacy of the processes to reduce Salmonella load for exportation to the U.S.